Pemanfaatan Digital Kufi Dalam Meningkatkan Technopreneurship Pada Organisasi Prisma - Annisa, Riski -; Rahayuningsih, Panny Agustia; Anna, Anna -; Maulana, Reza - (Universitas Pendidikan Ganesha, 2020)
Teenagers are a transition from childhood to adulthood, social skills and the ability to adjust to the more important when it was in adolescence. Failure of adolescents in mastering social skills will cause adolescents to have difficulty in adapting to the surrounding environment. Adolescence should be used to carry out many useful activities to be of use value, one of the useful activities is to introduce entrepreneurship education in youth so that in the future it can explore the creativity of adolescents. Based on that case, the team tried to give them some training on how to introduce and teach teenagers to design kufi and hopefully in the future it could make it a product that has a sale value. Training is given to administrators and members of the prism organization which is a youth organization of the al-amiin mosque. After the training is expected the participants can produce products that have a sale value.